Another Color Rendering Metric: Do We Really Need It, Can We Live without It?. Issue 1 (2nd April 2016) - de Beer, Esther; van der Burgt, Peter; van Kemenade, Johan
ABSTRACT: Most descriptions of the color rendering properties of light sources are based on the calculation of color differences for a number of reflectance samples between the light source and a reference source. The CIE color rendering index (CRI) is a single number based on the average color difference for eight reflectance samples. Since its introduction, the CRI has been discussed at length and many alternatives have been suggested to improve the description of color rendering. These metrics comprise among others, metrics based on color fidelity, color gamut, and color preference and combinations of these. All of these new proposals try to capture a certain color rendering aspect in a single number index to be used instead of or together with the existing CIE CRI. The "traditional" CRI has been criticized due to the fact that a single number index does not provide sufficient information about the color rendering properties of light sources. Creating a (second) single number metric seems to be a bit of a paradox, because it suffers from the same limitation by providing an average number to characterize certain color aspects for all colors. In our view, the best way to provide users of lighting in whatever application with accurate information on color characteristics is to provide specific information on the most important color characteristics such as hue, chroma, and lightness. In this article, we describe our methods of supplying hue-specific information via color rendering vectors and color rendering icons. We illustrate why we believe that it is important to add hue-specific information and what the shortcomings are of a second hue-averaged metric. We acknowledge that color appearance models have advanced since our first calculations and that it would be more appropriate to use CIECAM02. In addition, several recent papers have appeared discussing improved reflectance sample sets. These advancements, however, do not change the key message in this article, which advocates the use of graphics to communicate shifts in hue and chroma.